Prevention of Skin Disorders in Patients with Diabetes Mellitus Using Olive Oil in Semarang City - Ramdinar, Izkah Shafha; Anugrah Fajar Kartika Sari Khofifah; Anif Maghfiroh; Muhammad Hizrian Suryowicaksono; Muhammad Japar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Adolescence is a time when emotional development is still not fully established, particularly for adolescents living in orphanages. These individuals often experience more vulnerable and unstable emotions compared to their peers who live at home. Therefore, it's essential to find effective ways to manage these emotions, one of which is through expressive writing using the EXPRIT approach. The implementation of this activity is designed to provide adolescents with knowledge and develop their skills in emotional management, thereby improving their mental health and teaching them how to express their thoughts and feelings more effectively. The results of this activity showed a significant difference between the pre-test and post-test outcomes, as revealed by a paired sample t-test analysis. This indicates that the EXPRIT approach can be an effective method for helping adolescents at the Aisyiyah 4 Simo Boyolali orphanage manage their emotions.